2011
DOI: 10.1155/2011/305793
|View full text |Cite
|
Sign up to set email alerts
|

An Overview of Sensitization Dynamics in Ferritic Stainless Steel Welds

Abstract: Besides the problem of low ductility and poor notch toughness of ferritic stainless steel welds due to the microstructure characteristics of the weld section as a result of the weld heat input rate and the heat transfer factor, susceptibility to intergranular corrosion caused by the depletion of the chromium content of the weld matrix particularly in the HAZ is a major concern limiting the full deployment of the material in certain engineering applications regardless of its attractive economics combined with m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0
5

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 25 publications
0
24
0
5
Order By: Relevance
“…Due to this transformation, Xinzhong et al (2008) observed some martensite in the HAZ of 430 grade. As explained by Greeff and Du Toit (2006) then Amuda and Mridha (2011), a sensitization mechanism could have also occurred in the HAZ of FSS even with stabilizing elements. Titanium or niobium carbides could be partially dissolved at high temperature that led to the precipitation of chromium carbides during rapid cooling.…”
Section: Introductionmentioning
confidence: 72%
“…Due to this transformation, Xinzhong et al (2008) observed some martensite in the HAZ of 430 grade. As explained by Greeff and Du Toit (2006) then Amuda and Mridha (2011), a sensitization mechanism could have also occurred in the HAZ of FSS even with stabilizing elements. Titanium or niobium carbides could be partially dissolved at high temperature that led to the precipitation of chromium carbides during rapid cooling.…”
Section: Introductionmentioning
confidence: 72%
“…8 [tudija korozijske odpornosti zvarov je izredno pomembna za uspe{no uporabo feritnih nerjavnih jekel. Poleg obna{anja samega materiala v korozijskem mediju, je pomembna tudi korozijska odpornost zvarnih spojev.…”
Section: Uvodunclassified
“…Sensitization is a major problem in welding of SS that affects the alloys durability 1 . SS is commonly welded by resistance spot welding process process requires the application of both heat and pressure to achieve a sound joint.…”
Section: Introductionmentioning
confidence: 99%